2001
DOI: 10.1074/jbc.m100317200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Chronic Ethanol Treatment onN-Methyl-d-aspartate R1 Splice Variants in Fetal Cortical Neurons

Meena Kumari

Abstract: Functional N-methyl-D-aspartate receptors consisting of NR1 and NR2 subunits are an important site of action of ethanol. Chronic ethanol treatment increases the NR1 polypeptide levels in vivo and in vitro. Chronic ethanol treatment in vitro does not significantly alter the NR1 mRNA levels, even though under similar culture conditions ethanol (50 mM, 5 days) enhances the half-life of NR1 mRNA in fetal cortical neurons. To address this phenomenon, we determined by reverse transcriptionpolymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…For example, chronic ethanol was found to increase the levels of NR2B in the forebrain but not cerebral cortex (Narita and others 2000), in contrast to other studies that found that long-term voluntary ethanol intake increases the NR2B subunit in the cortex (Henniger and others 2003) and in cortical neurons (Kumari and Ticku 1998). Five days' incubation of cortical neurons with ethanol also resulted in increased level of NR1 spliced variants containing the C2′ cassette (Kumari 2001). A more recent study suggests that the expression level of NR1, but not NR2, is altered in the rat amygdala after chronic exposure to ethanol (Floyd and others 2003).…”
Section: Ethanol and Nmdarmentioning
confidence: 92%
“…For example, chronic ethanol was found to increase the levels of NR2B in the forebrain but not cerebral cortex (Narita and others 2000), in contrast to other studies that found that long-term voluntary ethanol intake increases the NR2B subunit in the cortex (Henniger and others 2003) and in cortical neurons (Kumari and Ticku 1998). Five days' incubation of cortical neurons with ethanol also resulted in increased level of NR1 spliced variants containing the C2′ cassette (Kumari 2001). A more recent study suggests that the expression level of NR1, but not NR2, is altered in the rat amygdala after chronic exposure to ethanol (Floyd and others 2003).…”
Section: Ethanol and Nmdarmentioning
confidence: 92%
“…Interestingly, another psychoactive substance, ethanol, has been reported to cause selective changes in the expression of exon 5-containing Nmethyl-D-aspartate NR1 splice variants in mouse fetal cortical neurons although the regulatory signals for the differential effects have not yet been identified. 33 Repeated MAP treatment results in an increase in the basal levels of the neocortical mrt1b mRNA at 2 and 3 weeks of withdrawal while a rapid and transient augmentation of the gene expression occurs after acute MAP administration. These data indicate that the repeated MAP-induced increase might be a long-lasting phenomenon and regulation of mrt1 transcription could be modified during or after the repeated treatment.…”
Section: Discussionmentioning
confidence: 99%
“…was performed as described (Kumari, 2001) to examine the effect of chronic alcohol treatment on the polypeptide levels of (i) NMDA R1 subunit of the NMDA receptor in the hippocampus and cerebral cortex and (ii) Cyp 2E1 apoprotein in liver. For NMDA R1 analysis, a known amount of tissue lysate (S1 fraction) (5 μg) from control and alcoholexposed cerebral cortices or hippocampi (n = 6) and protein standards were separated on 7.5% SDS-PAGE.…”
Section: Western Blot Analysismentioning
confidence: 99%